GAMBARAN BURNOUT PADA MAHASISWA JURUSAN KEPERAWATAN - Suha, Yantris; Nauli, Fathra Annis; Karim, Darwin (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022DO - 10.24843/coping.2022.v10.i03.p07, 2022)
Students majoring in nursing have a risk of experiencing burnout which a condition of physical, emotional, and mental exhaustion caused by demanding situations over a long period of time. This study aims to determine the description of burnout in nursing students at the Faculty of Nursing, Riau University. This study used a quantitative descriptive method. The sampling used stratified random sampling technique. The sample size is 243 respondents who suits the inclusion criteria. Analysis of the data used is univariate analysis using frequency distribution and percentage. The majority of respondents are female (93,8%), study based on their interests (73,6%). Number of respondents from the 2017 class was 66 people (27,2%), 2018 was 59 people (24,2%), 2019 was 58 people (23,8%), and 2020 was 60 people (24,6%). The majority of students experienced moderate level of burnout (66,7%). Based on the burnout dimension, the majority of students experienced moderate burnout on the emotional exhaustion dimension (74,5%) and decreased performance achievement (62,1%) and mild burnout on the depersolization dimension (58,4%). The majority of students experienced moderate level of burnout.